2019
DOI: 10.1186/s40816-019-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nociceptive and anti-inflammatory effects of an aqueous extract of blended leaves of Ocimum gratissimum and Psidium guajava

Abstract: Background: To investigate the antinociceptive and anti-inflammatory activities of aqueous extract of a blended mixture of dried leaves of Ocimum gratissimum and Psidium guajava, a traditional analgesic drug polyherbal (TADP) used as a remedy for pain-related conditions. Methods: Antinociceptive activity of TADP (100, 200 and 400 mg/kg) was evaluated in the hot plate test and acetic acid-induced nociception in mice while the anti-inflammatory was evaluated in carrageenan-induced paw oedema in rats. Levels of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…It has been demonstrated that ROS and RNS are able to decrease glutamate transporters activity and increase vanilloid and N -methyl-D-aspartate receptors activity [ 31 ]. Therefore, the antiradical properties of any substance may play an important role in the reduction of inflammatory nociception [ 32 ]. In our study, compounds 13b , but not 10b , at the medium and high doses decreased MPO level compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ROS and RNS are able to decrease glutamate transporters activity and increase vanilloid and N -methyl-D-aspartate receptors activity [ 31 ]. Therefore, the antiradical properties of any substance may play an important role in the reduction of inflammatory nociception [ 32 ]. In our study, compounds 13b , but not 10b , at the medium and high doses decreased MPO level compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify potential peripherally acting antinociceptive agents, this nociceptive model is quite efficient for dosages in which the analgesic and anti-inflammatory effects of drugs would be ineffective in other pain models ( Nock et al, 2022 ). When acetic acid is administered by intraperitoneal injection, peripheral nociception is induced upon direct activation of non-selective cationic channels or indirect release of different endogenous mediators namely, prostaglandins, cytokines, bradykinin, along with increased production of the enzymes lipoxygenase (LOX) and cyclooxygenase (COX) ( Alabi et al, 2019 ), thereby causing the stimulation of nociceptive neurons sensitive to the non‐steroidal anti-inflammatory drugs ( Prabhu et al, 2011 ). Therefore, this test can be utilized to look into novel mild analgesic non-steroidal anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This nociceptive model is extremely successful for dosages where the analgesic and anti-inflammatory effects of medication would be ineffective in other pain models 16 . Peripheral nociception is activated through the direct induction of non-selective cationic channels or the indirect secretion of various endogenous mediators, such as prostaglandins, cytokines, and bradykinin, as well as elevated production of lipoxygenase and cyclooxygenase enzymes resulting in the activation of neurons sensitive to nonsteroidal anti-inflammatory drugs (NSAIDs) 17,18 . Therefore, this test could be used to investigate the antinociceptive activity of novel NSAIDs.…”
Section: Discussionmentioning
confidence: 99%